ISSUES OF ATTRACTING PRIVATE CAPITAL IN BANK ACTIVITY AND STRENGTHENING THEIR RESOURCE BASE - Ernazarov Narmet Saparbayevich (Journals Park Publishing, 2023)
In the article, at the current stage of the liberalization and modernization of the economy in the Republic of Uzbekistan, the priority tasks of the banking system reform strategy are researched and the necessity, means, factors and effective measures of attracting private capital to the banking system are scientifically justified.
Keywords: bank, private capital, strategy, banking system, level of bank capitalization, resource.